Pulmonary Mucormycosis – An Experience from a Tertiary Care Center in Southern India: A PULM MUCOR Study - Ashwin Oliver Arul; K. Rajiv Karthik; Devasahayam Jesudas Christopher (Current Medical Issues)
Background: Pulmonary mucormycosis is a rare life-threatening fungal infection that primarily affects immunocompromised individuals, leading to severe morbidity and high mortality. The delta wave of the COVID-19 pandemic in India witnessed an alarming surge in mucormycosis cases, posing a significant health threat nationwide. This study aims to evaluate the risk factors, clinical features, radiological presentation, microbiology, diagnosis, complications, and outcomes of patients with pulmonary mucormycosis before and during the COVID-19 pandemic. Methodology: This study retrospectively analyzed case records of patients diagnosed with pulmonary mucormycosis who presented to the departments of pulmonary medicine, respiratory medicine, and infectious diseases at a large 3000-bed tertiary teaching hospital in Southern India between 2012 and 2022. Results: Among the 37 patients with pulmonary mucormycosis, 24 (65%) were male, and 13 (35%) were female, with a mean age of presentation of 50.5 years. There were 25 cases of non-COVID-19-associated pulmonary mucormycosis (CAPM) and 12 cases of CAPM. The most common risk factor was diabetes in 34 patients (91%), with the mean glycosylated hemoglobin A1C (HbA1C) at presentation being 10.28. History of steroid use was present in 9 (24%) patients, predominantly among those with CAPM. Cough was the most frequent presenting symptom seen in 27 (73%), followed by fever 24 (64%), dyspnea 11 (30%), and hemoptysis 6 (16%). The most common computed tomography (CT) scan findings were consolidations and cavitations. Majority of the samples 25/37 (67%) were acquired using bronchoscopy. Rhizopus arrhizus was the most commonly isolated species. All patients received systemic antifungal therapy with amphotericin and posaconazole. However, only four patients (11%) underwent combined surgical treatment along with appropriate antifungal agents. The overall mortality in this study was 15/37 (41%). Conclusions: Pulmonary mucormycosis requires a high index of suspicion, and a delay in the diagnosis leads to complications and poor outcomes. Uncontrolled diabetes mellitus and chronic kidney disease were the conventional predisposing factors for pulmonary mucormycosis. However, CAPM was associated with both diabetes and steroid usage. Early identification of the disease is the key, and an early referral for bronchoscopy in a susceptible host can shorten the time to diagnosis and probably improve outcomes. Treatment requires a multipronged approach with control of risk factors, appropriate antifungal therapy, and aggressive early surgery where feasible.